Myopia as a problem of the modern world. Methods of treatment and prevention - Marcelina Szewczyk; Julia Ufnal; Dominika Rosińska-Lewandoska; Dominika Lewandowska; Klaudia Kożuchowska; Dawid Pilarz; Maria Morawska; Anna Wolff; Szymon Gruszka; Kinga Jarosz (Journal of Education, Health and Sport)
Introduction and objective